2006
DOI: 10.1038/nature04854
|View full text |Cite
|
Sign up to set email alerts
|

The giant electromechanical response in ferroelectric relaxors as a critical phenomenon

Abstract: The direct conversion of electrical energy to mechanical work by a material is relevant to a number of applications. This is illustrated by ferroelectric 'relaxors' such as Pb(Mg(1/3)Nb(2/3))O(3)-PbTiO(3) (PMN-PT; refs 5, 6): these materials exhibit a giant electromechanical (piezoelectric) response that is finding use in ultrasonic and medical applications, as well as in telecommunications. The origins of this effect are, however, still unclear. Here we show that the giant electromechanical response in PMN-PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
440
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 675 publications
(463 citation statements)
references
References 16 publications
20
440
2
1
Order By: Relevance
“…An emerging trend is that magnetostriction enhancement in Fe based systems occurs for compositions near structural phase boundaries. An analogy with giant electrostriction of ferroelectric solid solution and relax ors 22,23 also points to the intriguing possibility that some structural boundaries in magnetic materials can act as property enhancing morphotropic phase boundaries. Indeed, Yang et al have reported a rhombohedral/tetragonal morphotropic phase boundary with enhanced magnetostrictive properties in the TbCo 2 -DyCo 2 sys tem occurring below 160 K (ref.…”
mentioning
confidence: 96%
“…An emerging trend is that magnetostriction enhancement in Fe based systems occurs for compositions near structural phase boundaries. An analogy with giant electrostriction of ferroelectric solid solution and relax ors 22,23 also points to the intriguing possibility that some structural boundaries in magnetic materials can act as property enhancing morphotropic phase boundaries. Indeed, Yang et al have reported a rhombohedral/tetragonal morphotropic phase boundary with enhanced magnetostrictive properties in the TbCo 2 -DyCo 2 sys tem occurring below 160 K (ref.…”
mentioning
confidence: 96%
“…It is remarkable that a single family of PbTiO 3 based perovskite materials, such as lead zirconate titanate PbZr 1−x Ti x O 3 (PZT) [1][2][3][4] and a variety of lead-based relaxor ferroelectrics, 1,5,6 is dominating the field of ferroelectric (FE) and piezoelectric applications. Outstanding polar, piezoelectric and dielectric properties of all of these compounds emanate from strong lattice distortions -specifically, large displacements of both Pb 2+ and Ti 4+ ions away from their centrosymmetric positions in the undistorted perovskite structure.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted, however, that an electric field induced nucleation of an O phase at expense of the T phase 321 or a change in the relative content of R and T phases cannot be discarded. The peak in piezoelectric response observed above marked with indicates that the electric field induced paraelectric to ferroelectric transitions in BZT-BCT are of first order 156,188,191 , which is supported by the non-zero thermal hysteresis in dielectric properties. 194 The high 33 values above that were obtained at finite bias-fields ( 33 ) = (0.40 ± 0.12) kV/mm implies a line of critical points.…”
Section: Bias-field-and Temperature-dependent Quasi-static Small Signmentioning
confidence: 67%
“…194 The high 33 values above that were obtained at finite bias-fields ( 33 ) = (0.40 ± 0.12) kV/mm implies a line of critical points. [188][189][190][191] This observation casts doubt on the assertion that triple points of the zero-field pseudo-binary phase diagram are also tricritical points. 194,333 In order to allow a better understanding of the strain mechanisms in BZT-BCT, quantification of the intrinsic and extrinsic contributions to 33 .3 is valid with the assumption that reversible switching is considerably reduced at zero bias-field.…”
Section: Bias-field-and Temperature-dependent Quasi-static Small Signmentioning
confidence: 72%
See 1 more Smart Citation